Spindle cell rhabdomyosarcoma of the tongue – A rare entity - Khadim, MT; Asif, A; Ali, Z; Jamal, S; Rizwan, - (Journal of College of Medical Sciences-Nepal, 2012)
Spindle cell variant of Rhabdomyosarcoma is a rare malignant tumor in adults but even more so in tongue. We report a case of a 17 year old boy who presented with a polypoidal swelling on the tip of the tongue. The mass was excised and the specimen was sent to the Histopathology Department of Armed Forces Institute of Pathology for Histomorphological diagnosis. The histological evaluation showed a malignant spindle cell tumor. On the basis of morphological features and immunohistochemistry findings a final diagnosis of Rhabdomyosarcoma, Spindle cell variant was made. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 63-66 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6814